High‐level production of wild‐type and oxidation‐resistant recombinant alpha‐1‐antitrypsin in glycoengineered CHO cells. Issue 9 (25th May 2022) - Koyuturk, Izel; Kedia, Surbhi; Robotham, Anna; Star, Alexandra; Brochu, Denis; Sauvageau, Janelle; Kelly, John; Gilbert, Michel; Durocher, Yves
Abstract: Alpha‐1‐antitrypsin (A1AT) is a serine protease inhibitor which blocks the activity of serum proteases including neutrophil elastase to protect the lungs. Its deficiency is known to increase the risk of pulmonary emphysema as well as chronic obstructive pulmonary disease. Currently, the only treatment for patients with A1AT deficiency is weekly injection of plasma‐purified A1AT. There is still today no commercial source of therapeutic recombinant A1AT, likely due to significant differences in expression host‐specific glycosylation profile and/or high costs associated with the huge therapeutic dose needed. Accordingly, we aimed to produce high levels of recombinant wild‐type A1AT, as well as a mutated protein (mutein) version for increased oxidation resistance, with N ‐glycans analogous to human plasma‐derived A1AT. To achieve this, we disrupted two endogenous glycosyltransferase genes controlling core α−1, 6‐fucosylation ( Fut8 ) and α−2, 3‐sialylation ( ST3Gal4 ) in CHO cells using CRISPR/Cas9 technology, followed by overexpression of human α−2, 6‐sialyltransferase ( ST6Gal1 ) using a cumate‐inducible expression system. Volumetric A1AT productivity obtained from stable CHO pools was 2.5‐ to 6.5‐fold higher with the cumate‐inducible CR5 promoter compared to five strong constitutive promoters. Using the CR5 promoter, glycoengineered stable CHO pools were able to produce over 2.1 and 2.8 g/L of wild‐type and mutein forms of A1AT, respectively, with N ‐glycans analogous to the plasma‐derived clinical product Prolastin‐C. Supplementation of N ‐acetylmannosamine to the cell culture media during production increased the overall sialylation of A1AT as well as the proportion of bi‐antennary and disialylated A2G2S2 N ‐glycans. These purified recombinant A1AT proteins showed in vitro inhibitory activity equivalent to Prolastin‐C and substitution of methionine residues 351 and 358 with valines rendered A1AT significantly more resistant to oxidation. The recombinant A1AT mutein bearing an improved oxidation resistance described in this study could represent a viable biobetter drug, offering a safe and more stable alternative for augmentation therapy. Abstract : Therapeutic alpha‐1‐antitrypsin (A1AT) is currently manufactured following fractionation of human serum from blood donors (e.g., Prolastin). Expression systems allowing for high‐level production of A1AT with glycosylation similar to human plasma‐derived A1AT are needed. The authors develop glycoengineered CHO cells allowing for the production of up to 3 g/L of oxidation‐resistant recombinant A1AT with glycosylation resembling that of plasma‐derived A1AT. This may represent a cost‐effective approach for manufacturing recombinant A1AT for clinical applications. (Figures produced using Servier Medical Art/A1AT model by Thomas Shafee—Own work, CC BY 4.0, https://commons.wikimedia.org/w/index.php?curid=64356167 ).